The Virtual Sales Handbook - Nymand, Christian; Kvedare, Mante (Ascent Audio, 2021)
Learn to engage your B2B customers through effective virtual sales meetings and presentations The global COVID-19 pandemic has radically changed how business-to-business companies interact with their customers. The traditional face-to-face meeting has quickly become a thing of the past-the virtual customer engagement model is the new normal. To secure existing and future revenue streams in the virtual B2B sales environment, companies must equip their commercial frontline with the confidence, skills, and tools necessary for effectively engaging customers virtually. The Virtual Sales Handbook: A Hands-on Approach to Engaging Customers is designed for sales reps, commercial managers, customer relationship managers, and other customer-facing professionals working in the virtual realm. Step-by-step, listeners learn to prepare for a virtual sales meeting, create compelling virtual presentations, build energy through effective openers, develop trust in the virtual world, drive impact through virtual meeting follow-up, and much more. Throughout the book, listeners are provided with an abundance of tips and tricks, illustrative examples and case studies, and actionable strategies based on extensive implementation and upskilling experience.